32 Effects of kinesio® taping on ankle complex stability and dynamic postural control in female ballet dancers. (12th October 2015) - Kovaleski, JE; Botsis, AE; Gurchiek, LR; Ellis, D; Liu, W; Rooney, C; Hollis, JM
Abstract : Background: Ankle sprain is the most commonly diagnosed injury experienced by ballet dancers. Traditional taping and bracing affect function by restricting range of motion but are aesthetically unappealing as practical modes of injury prevention for ballet dancers. Few studies have investigated alternative support measures such as Kinesio® taping. Objective: The purpose of this study was to determine the effects of Kinesio® taping on ankle complex motion and stiffness and dynamic postural control in ballet dancers. Design: Cross-sectional study. Setting: University research laboratory. Participants: Twelve healthy, non-professional female ballet dancers with a mean experience dancing en pointe of 5.9 years and successful performance of ballet jumping. Interventions: Participants performed 3 ballet jumps ( sauté arabesque, sissonne ouverte de côté, and sissonne ouverte an evant ) with single-leg landings on a force plate across 3 ankle support conditions (Kinesio® taping [KT], sham-KT [ST], and no tape [NT]). Subjects were taped for prevention of a lateral ankle sprain with three strips of Kinesio® tape applied with the foot held in full dorsiflexion. Sagittal and frontal plane motion and load-displacement of the ankle complex for each support condition were obtained using an ankle arthrometer. Main outcome measurements: Dependent variables included measurements of ankle complex motion and stiffness and jump landing time to stabilisation in the anterior/posterior, medial/lateral, and vertical directions using the unbounded third order polynomial method. Results: KT (28.2 ± 6.7°) restricted ( P < 0 .001) inversion motion when compared to ST (32.7 ± 5.7°) and NT (35.9 ± 9.1°) and increased inversion stiffness (0.167 ± 0.073 N·m/°) compared to ST (0.111 ± 0.038 N·m/°) and NT (0.102 ± 0.042 N·m/°). KT was not found to have a significant effect (.05) on dynamic postural control. Conclusions: The results demonstrate that Kinesio® taping restricted frontal plane ankle complex motion that is associated with lateral ankle sprain. Objective information on the amount and nature of ankle tape application may assist sports medicine practitioners when recommending ankle support to athletes.